Կոմմագենեի դրամներում հայկական թագի մեկնությունների հարցը ֆրանսիական պատմագրության մեջ - Ա. Վ. Դումիկյան (ՀՀ ԳԱԱ հրատ.)
В 19веке вo французской нумизматической литературе уже была принята идея родства царей Великой Армении и Коммагены. Исследования французских нумизматов, посвященные вопросу армянского происхождения тиары, явились значительным вкладом в историю армянской нумизматики. In the 19th century in the French numismatic literature the idea of kinship of the sovereigns of the kingdoms of Great Armenia and Commmagene had already been available. The researches of the French numismats on the Armenian tiara contributed considerably to the history of the Armenian numismatics.
Keywords: History; Auxiliary Sciences of History; Numismatics; D History